If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -1x = -25 Solving 5t + -1x = -25 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 'x' to each side of the equation. 5t + -1x + x = -25 + x Combine like terms: -1x + x = 0 5t + 0 = -25 + x 5t = -25 + x Divide each side by '5'. t = -5 + 0.2x Simplifying t = -5 + 0.2x
| 4(-2.317073172)-7(1.390243902)=-19 | | 3(x-2)=-7.5 | | 7[3-(-4x-9)]=224x+525 | | -1+x=2(x-1) | | -7ln(2x)=-28 | | (1-x)-5=10 | | 7=2(9+6) | | -3x+11=96x-88 | | 45n=-9 | | 26/39=x/30 | | 4x-7(1.390243902)=-19 | | 17-x/3=28 | | 4x-10/3=2 | | 72=8/3x | | y=12x=6/7 | | 16+6y=9 | | 6.25/x=1.25 | | 4569+1.8x=0 | | x/8-7=3 | | 23/46=x/16 | | 1+9a=8a+8 | | (X+5)p(x)=2x^2-6x-1 | | -40+12m=4(5m-4) | | 25+y=12 | | -8+c=40 | | -7(-4.75+-1.75y)-2y=19 | | 6x+11+4x+2 = (6x+11)+(4x+2) | | 10x-28=20+7x | | (-2.75)(1.6)= | | 12u-3-4u=3 | | 24a-22=-(4-24a) | | x^2+9x+18=x^2+5x+6 |